Boron(II) cations: Interplay between Lewis-pair-acceptor and electron-donor properties - Widera, Anna; Vogler, Daniel; Wadepohl, Hubert; Kaifer, Elisabeth; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2018)
Boron(III) cations are widely used as highly Lewis acidic reagents in synthetic chemistry. In contrast, boron(II) cations are extremely rare and their chemistry almost completely unknown. They are both Lewis acids and electron donors, properties that are commonly associated with catalytically active late-transition-metal complexes. This double reactivity pattern ensures a rich and diverse chemistry. Herein we report the facile synthesis of several new boron(II) cations starting with a special diborane with two easily exchangeable triflate substituents. By increasing the π-acceptor character of the neutral σ-donor reaction partners, first reactions were developed in which the combined Lewis acidity and electron-donor properties of boron(II) cations are applied for the reduction of organic molecules. The results of our study pave the way for applications of these unusual compounds in synthetic chemistry.